Hubungan antara Lama Terinfeksi Virus Penderita Hepatitis B dengan Indeks Eritrosit (MCV,MCH,MCHC) - Septiani, Erna; Maruni Wiwin Diarti; Erlin Yustin Tatontos; Fihiruddin (Poltekkes Kemenkes Mataram, 2024)
Background: Hepatitis B is an infectious disease that attacks the liver caused by the Hepatitis B virus. Hepatitis B virus infection is very infectious and is the main cause of chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma. Hepatitis B can cause liver cirrhosis, where there is a change in the structure of the liver parenchyma resulting in a decrease in erythrocyte index levels. Objective: To determine the relationship between the duration of viral infection in hepatitis sufferers and the erythrocyte index (MCV, MCH, MCHC) Method: This research is an analytical observational study with a cross sectional approach and accidental sampling technique Results: Based on the results of the Kruskall Wallis test, the relationship between the duration of infection with the hepatitis B virus and the erythrocyte index (MCV, MCH, MCHV) resulted in MCV 75.50, MCH 17.97, MCHC 43.03 with a p value = 0.000 < 0.05. so it can be concluded that there is a relationship between the duration of infection with the hepatitis B virus and the erythrocyte index (MCV, MCH, MCHV) Conclusion: From the results of the analysis carried out, there is a relationship between the duration of infection with the hepatitis B virus and the erythrocyte index (MCV, MCH, MCHV)